A mathematical model for estimating the axial stress of the common carotid artery wall from ultrasound images - Soleimani, Effat; Mokhtari-Dizaji, Manijhe; Saberi, Hajir; Sharif-Kashani, Shervin (Medical & biological engineering & computing, 2016)
Clarifying the complex interaction between mechanical and biological processes in healthy and diseased conditions requires constitutive models for arterial walls. In this study, a mathematical model for the displacement of the carotid artery wall in the longitudinal direction is defined providing a satisfactory representation of the axial stress applied to the arterial wall. The proposed model was applied to the carotid artery wall motion estimated from ultrasound image sequences of 10 healthy adults, and the axial stress waveform exerted on the artery wall was extracted. Consecutive ultrasonic images (30 frames per second) of the common carotid artery of 10 healthy subjects (age 44 ± 4 year) were recorded and transferred to a personal computer. Longitudinal displacement and acceleration were extracted from ultrasonic image processing using a block-matching algorithm. Furthermore, images were examined using a maximum gradient algorithm and time rate changes of the internal diameter and intima-media thickness were extracted. Finally, axial stress was estimated using an appropriate constitutive equation for thin-walled tubes. Performance of the proposed model was evaluated using goodness of fit between approximated and measured longitudinal displacement statistics. Values of goodness-of-fit statistics indicated high quality of fit for all investigated subjects with the mean adjusted R-square (0.86 ± 0.08) and root mean squared error (0.08 ± 0.04 mm). According to the results of the present study, maximum and minimum axial stresses exerted on the arterial wall are 1.7 ± 0.6 and −1.5 ± 0.5 kPa, respectively. These results reveal the potential of this technique to provide a new method to assess arterial stress from ultrasound images, overcoming the limitations of the finite element and other simulation techniques.